USING WORD GAME AS THE INTERESTING WAY FOR STUDENT TO LEARNING AND ENRICH VOCABULARIES - Ayu Mulianti (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Learning and enrich vocabularies are two important point that have major rule for support to use of language. For non-native English, learning English as their foreign language needs extra learning. Many avenues offered for learning English mainly for enrich vocabularies that we have. In many cases, the common ways for learning vocabularies like reading English literature and join English class still difficult to understand to non-native English. However, this problem has conventional solve way like watching a movie although that ways still difficult to understand for some people. Thus, a more interesting way to learning and enrich vocabularies is effective way to be used. According, to the researcher suggests word game would be an interesting way to learning and enrich English vocabularies. Scrabble is board games that play with words and it famous because this game indicates the level of intellectual. This game may gives new challenge especially for new player to use their English with minimum word that they get randomly in a pocket word. The researcher used library method obtained from internet browsing for analyzed a word game “Scrabble” to undertaken seek the rule of this game to learning and enrich vocabularies. In this paper, researcher attempted to find a more interesting way to learning and enrich English vocabularies as foreign language by using word game.